FENOMENOLOGI KOMUNIKASI INKLUSIF PADA BARISTA TEMAN TULI DI KAFE KOPI TUTUR RASA SURABAYA - Saputra, Alan Damar; Heidy Arviani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the experience and meaning-making of inclusive communication in the work environment of Deaf baristas at Kopi Tutur Rasa Café, Surabaya. Using a qualitative phenomenological approach grounded in Alfred Schutz's perspective and symbolic interactionism theory, data were collected through in-depth interviews, participant observation, and documentation involving six informants: two Deaf baristas, two internal café staff, and two customers, selected through source triangulation. The findings show that the experience of inclusive communication is formed through three themes, namely equality in communication, communication adaptation, and social stigma, while the meaning-making of inclusive communication is formed through three themes, namely language barriers, equality as a shared value, and open interaction as a form of self-transformation. Communication equality is built through reciprocal effort between Deaf and hearing individuals, supported by adaptive media such as BISINDO sign language, visual cue cards, and text messaging. Social stigma toward the capability of Deaf workers in public service gradually diminishes through consistent direct interaction. This study concludes that inclusive communication at Kopi Tutur Rasa is not merely an exchange of messages between parties with different hearing abilities, but a continuous social process built through acceptance, adjustment, collaboration, and equal opportunity that transforms self-perception among Deaf baristas, coworkers, and customers alike.